Preferensi konsumsi keluarga perspektif ekonomi Islam (Studi kasus di kelurahan Wates, Ngaliyan Kota Semarang) - Mansur Mansur (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
This study aims to determine the consumption preference of Moslem family in Wates Ngaliyan Semarang in the perspective of Islamic economics and the factors that influence the consumption preference of Moslem family in Wates Ngaliyan Semarang. This research is field research using descriptive qualitative approach. The results of this research are that family consumption preference still over consumption or israf, but there are some Moslem families suitable to consumption preference in Islam, and There is other factor influencing consumption preference which is social environment.